2016
DOI: 10.1177/1071100716646629
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Talar Anatomy and Subtalar Joint Alignment on Weightbearing Computed Tomography With Radiographic Flatfoot Parameters

Abstract: Level III, case-control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
64
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 16 publications
(35 reference statements)
1
64
0
1
Order By: Relevance
“…Studies using single weight‐bearing CT images showed significant differences in the orientation of the posterior facet from anterior to posterior (screw shape morphology) . We found similar results using DRRs: The posterior aspect of the joint (45/10 degrees Broden view) showed a more varus inclination compared to the anterior aspect, which was in a more neutral alignment.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Studies using single weight‐bearing CT images showed significant differences in the orientation of the posterior facet from anterior to posterior (screw shape morphology) . We found similar results using DRRs: The posterior aspect of the joint (45/10 degrees Broden view) showed a more varus inclination compared to the anterior aspect, which was in a more neutral alignment.…”
Section: Discussionsupporting
confidence: 73%
“…The role the subtalar joint plays in the development of ankle joint disorders has been investigated extensively in recent years . It has been suggested that the subtalar joint morphology (e.g., convex vs. flat) and orientation (e.g., slope) specifically of the posterior facet may influence the evolution of ankle osteoarthritis .…”
mentioning
confidence: 99%
See 3 more Smart Citations